2019
DOI: 10.1002/smi.2879
|View full text |Cite
|
Sign up to set email alerts
|

The associations between alexithymia, non‐suicidal self‐injury, and risky drinking: The moderating roles of experiential avoidance and biological sex

Abstract: Alexithymia and experiential avoidance are personality traits regularly identified as correlates of behaviours that serve an emotion regulatory function, including, nonsuicidal self-injury (NSSI) and risky drinking. In the current study, we examined whether the relationships between alexithymia, NSSI, and risky drinking are moderated by experiential avoidance and sex. A sample of 778 university students (77.1% female, M age = 22.27, SD = 6.71) completed online questionnaires. For men, a combination of high lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 41 publications
(57 reference statements)
1
17
1
Order By: Relevance
“…The remaining study used the Alexithymia Questionnaire for Children (Rieffe, Oosterveld & Terwogt, 2006) which was derived from the TAS20 to be suitable for younger participants. Four studies only reported one or more TAS20 subscales (Difficulty Identifying Feelings [DIF], Difficulty Describing Feelings [DDF], and Externally Orientated Thinking [EOT]) rather than total TAS20 (Anderson & Crowther, 2012; Cerutti, Zuffianò & Spensieri, 2018; Greene, Hasking & Boyes, 2019; Hsu, Chen & Lung, 2013). The other studies all reported total TAS20, with (10 studies) or without (16 studies) the subscale scores.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The remaining study used the Alexithymia Questionnaire for Children (Rieffe, Oosterveld & Terwogt, 2006) which was derived from the TAS20 to be suitable for younger participants. Four studies only reported one or more TAS20 subscales (Difficulty Identifying Feelings [DIF], Difficulty Describing Feelings [DDF], and Externally Orientated Thinking [EOT]) rather than total TAS20 (Anderson & Crowther, 2012; Cerutti, Zuffianò & Spensieri, 2018; Greene, Hasking & Boyes, 2019; Hsu, Chen & Lung, 2013). The other studies all reported total TAS20, with (10 studies) or without (16 studies) the subscale scores.…”
Section: Resultsmentioning
confidence: 99%
“…Of the eight studies that were based on university student samples, all reported significant and positive associations between self‐harm and alexithymia (total and/or subscales) (Anderson & Crowther, 2012; Borrill, Fox, Flynn & Roger, 2009; Greene et al ., 2019; Hasking & Claes, 2019; Oskis & Borrill, 2019; Paivio & McCulloch, 2004; Polk & Liss, 2007; Wester & King, 2018). Among those that reported the subcomponents of alexithymia, all found DIF to be significantly higher in those with a history of self‐harm (Anderson & Crowther, 2012; Borrill et al ., 2009; Greene et al ., 2019; Oskis & Borrill, 2019). The findings regarding DDF were more mixed with two studies finding a significant positive association (Borrill et al ., 2009; Greene et al ., 2019) and one reporting a non‐significant result (Oskis & Borrill, 2019), while all those which measured EOT reported a non‐significant relationship with self‐harm.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent systematic review and meta-analysis found that the association between alexithymia and NSSI may be stronger for women (Greene et al, 2020) and another study (Greene et al, 2019) found that men who had difficulties describing feelings were more likely to engage in risky drinking than NSSI. It is possible that these sex differences may be explained by different anticipated outcomes of NSSI and risky drinking for men and women.…”
Section: Sex Differencesmentioning
confidence: 99%
“…Regardless of the shared emotion regulatory function, limited research has directly compared NSSI to risky drinking (e.g., Greene, Hasking, & Boyes, 2019;Hasking, 2017;Kingston et al, 2010). Yet, by taking a transdiagnostic approach to identify and understand shared factors between NSSI and risky drinking, we can target these shared factors in intervention initiatives and possibly reduce the odds of an individual shifting between dysregulated behaviours (Duggan & Heath, 2014).…”
Section: Introductionmentioning
confidence: 99%